2021
DOI: 10.1186/s13075-021-02556-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma interferon-alpha is associated with double-positivity for autoantibodies but is not a predictor of remission in early rheumatoid arthritis—a spin-off study of the NORD-STAR randomized clinical trial

Abstract: Background The type I interferon (IFN) gene signature is present in a subgroup of patients with early rheumatoid arthritis (RA). Protein levels of IFNα have not been measured in RA and it is unknown whether they associate with clinical characteristics or treatment effect. Methods Patients with early untreated RA (n = 347) were randomized to methotrexate combined with prednisone, certolizumab-pegol, abatacept, or tocilizumab. Plasma IFNα protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
2
6
1
Order By: Relevance
“…IFN-α associated with raised ESR in our cohort and in other autoimmune conditions12 but is also relevant prior to onset of inflammation as an IGS predicts progression to RA in ‘at risk’ cohorts 19–21. Furthermore, autoantibodies predate clinical presentation, and we demonstrate a clear association between IFN-α and RF titres in eRA consistent with previous observations in autoimmunity 12 17. In contrast, there was no association between IFN-α and ACPA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…IFN-α associated with raised ESR in our cohort and in other autoimmune conditions12 but is also relevant prior to onset of inflammation as an IGS predicts progression to RA in ‘at risk’ cohorts 19–21. Furthermore, autoantibodies predate clinical presentation, and we demonstrate a clear association between IFN-α and RF titres in eRA consistent with previous observations in autoimmunity 12 17. In contrast, there was no association between IFN-α and ACPA.…”
Section: Discussionsupporting
confidence: 89%
“… 16 Furthermore, both IGS and serum IFN-α levels fall in parallel with clinical response over 6 months, additionally supporting the role of IFN-α driving the IGS in eRA. Like others, 17 and in contrast to the IGS, we could not demonstrate an association of baseline IFN-α with longitudinal clinical outcomes. A potential explanation is that the IRG integrates activity over time of IFN-α, which itself has a short half-life.…”
Section: Discussioncontrasting
confidence: 84%
“…Recently, type I interferon (IFN-I) and interferon gene signatures (IGSs) have drawn considerable attention in RA. 36,56,57 Emerging evidence has shown that circulating IFN-α is primarily responsible for IGSs in the peripheral blood of drug-naive patients with eRA, and baseline IGS is associated with 6-month DAS-28 and ESR. However, circulating IGSs were not associated with disease activity in established RA.…”
Section: Discussionmentioning
confidence: 99%
“…IFNα is another major type I IFN, but it was not selected in the present study 22 . Whether there are differences in the pathophysiological action of these two cytokines in RA or a switch-on role of early relapse in RA needs to be elucidated; patients with a high baseline IFNβ/α ratio showed poorer response to TNF inhibitors in RA 23 .…”
Section: Discussionmentioning
confidence: 99%